Value Capture in the Face of Known and Unknown Unknowns - Kevin A. Bryan; Michael D. Ryall; Burkhard Schipper (University of California, Department of Economics, 2019)
A large theoretical literature on value capture following Brandenburger and Stuart (1996) uses cooperative games under complete information to study how and why firms earn supernormal profits. However, firms often have different information, beliefs, or creative foresight. We extend value capture theory to incomplete information ("known unknowns") or unawareness ("unknown unknowns"), and illustrate some conceptual issues with that extension. Using the case study of Cirque du Soleil, we show how an entrepreneurial firm can profit even when it does not contribute materially to value creation. In a case study of Apple iTunes, we show how value capture depends quantitatively on the beliefs of other firms.
Keywords: D21; D83; C71; 330; cooperative games; unawareness; incomplete information; coarse core; business strategy; value-capture theory